CHARISMA IN THE CLOUD: Digital Ulama, Attention Economy, and the Mediatized Construction of Islamic Marriage in Indonesia - A'isyah A'isyah (UIN Sumatera Utara, 2026)
This study analyses how Indonesian online preachers construct and disseminate marriage discourse and digital fatwas within the expanding landscape of Digital Islam. Unlike traditional ulama such as Gus Baha, Abdul Somad, and Buya Yahya-whose authority emerges from pesantren networks, textual mastery, and communal patronage-digital preachers gain legitimacy through visibility, virality, and emotional engagement. Examining influential online preachers and their marriage-related content from 2020 to 2025, the study shows that marriage has become a central normative theme increasingly shaped by the political economy of digital capitalism. Digital platforms restructure religious narratives, regulate the circulation of meaning, and commodify Islamic teachings on morality, family, and gender. These shifts indicate a broader crisis of Islamic authority, as legitimacy moves from textual expertise toward algorithmic popularity. By integrating Weber's charismatic authority, Hjarvard and Fuchs's mediatization theories, and Foucault's discourse-power framework, the study argues that digital fatwas serve as sites of both symbolic and material power in Indonesia's contested digital public sphere.